Hardness gradient layer on pure titanium based on the prefabricated TiB whiskers. Issue 17 (1st September 2021) - Lu, Yaoping; Qu, Deyi; Duan, Yonghua; Peng, Mingjun
Abstract: A new route based on the prefabricated TiB whiskers has been explored to prepare a hardness gradient layer on pure titanium. By optimizing the formation conditions of boriding and aluminizing, a hardness gradient layer composed of TiB2 layer, TiB whiskers + TiAl3 layer, TiAl3 layer, and diffusion layer, with the thickness of 102 μm and the maximum microhardness of 2410 HV0.01, was successfully fabricated on pure titanium. From the surface to the matrix, the hardness gradient layer had a gradual decrease in hardness, which can improve the protection effect of surface layer on the matrix and increase the service stability of titanium and its alloys.